FV 7. Cross-sectional area of the vagus nerve correlates with parasympathetic dysfunction in Parkinson's Disease. Issue 8 (August 2021) - Huckemann, S.; Müller, K.; Averdunk, P.; Kühn, E.; Hilker, L.; Kools, S.; Scholz, L.; Bulut, Y.; Brünger, J.; Grüter, T.; Fisse, A.L.; Motte, J.; et al.
Abstract : Introduction . In this study we evaluated the autonomic neural function in Parkinson's disease (PD) by combining the use of clinical scoring, functional evaluation with head-up tilt test (HUTT) and morphological studies of the vagus nerve (VN) with nerve ultrasound (NU). This allowed us to correlate morphological changes of the VN with markers of parasympathetic dysfunction from HUTT. Patients/Methods. In our study we used NU to compare the mean values of the cross-sectional area (CSA) of the VNs of 80 PD patients with those of controls (n=40) and patients with chronic inflammatory demyelinating polyneuropathy (CIDP) (n=76). In 69 cases HUTT data was analyzed concerning the presence of orthostatic hypotension (OH), postural orthostatic tachycardia syndrome (POTS) and chronotropic incompetence (CI). Functional haemodynamic parameters in HUTT were used to evaluate parasympathetic functions and correlate them with VN CSA (n=65). Results . In PD, the CSA of right / left VN was significantly smaller compared to the right/left VN of the control and CIDP patients (Table 1). Based on HUTT, 60.5 % of the patients were diagnosed with autonomic dysfunction (OH n=11, CI n=31, POTS n=1). Patients with OH showed significantly higher UPDRS-III values than those with CI (p=0.025). The CSA of the VN correlated inversely with heart rate and positively with parameters representing parasympathetic modulation through vagal activity (Fig. 1). Conclusion . By using NU significant morphological differences of the CSA of the VN were detected in CIDP, PD and a healthy control group. Furthermore, we demonstrated for the first time that anatomical characteristics of the VN correlate with parameters of parasympathetic function from the spectral analysis of cardiovascular parameters in HUTT for PD. This finding enables a new interpretation of the anatomical characteristics of the VN for PD patients and diagnosis of autonomic dysfunction. Fig. 1. Schematic presentation of the inverse correlation of the cross-sectional area of the right vagus nerve with the heart rate. Positive correlation with markers of parasympathetic activity HFnu-RRI. (Spearman Correlation). Abbreviations: HR=heart rate, HFnuRRI = high frequency power of the RR-Interval, bpm= beats per minute, CSA= cross-sectional area Table 1. Demographical and epidemiological characteristics as well as the cross-sectional area (CSA) of the vagus nerve. All values are provided as mean ± standard deviation. Abbreviations: INCAT/ODSS = inflammatory neuropathy cause and treatment/overall disability sum score, MDS-UPDRS III= MDS-Unified Parkinson's Disease Rating Scale, SCOPA-AUT= Scales for Outcomes in Parkinson's Disease- Autonomic Dysfunction, PDQ39 = Parkinson's Disease Questionnaire, CSA = cross sectional area.